Locally compact space and continuity - Choudhary, Shitanshu Shekhar; Thapa, Raju Ram (BIBECHANA, 2010)
Topological spaces for being T0, T1, T2 and regular space have been discussed. The conditions for a topological space to be locally compact have also been studied. We have found that a continuous function preserves locally compactness. Keywords: Topological spaces; Compactness; Regular space DOI: 10.3126/bibechana.v7i0.4038 BIBECHANA 7 (2011) 18-20